Students' Mathematical Problem Solving Ability in terms of Independent Learning in the Eliciting Activities Model (MEAs) - Anisa Rima Auliya; Iwan Junaedi; Bambang Eko Susilo (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
This study aims to describe the mathematical problem-solving ability of class VIII B students in learning independence in the Eliciting Activities Model (MEAs). This research method uses the descriptive qualitative method. The research subjects were students of class VIII B of MTs Muhammadiyah 7 Purbalingga, which consisted of two students for each category. The data in this study were taken with a problem-solving ability test and a learning independence questionnaire, which was processed through three stages: data reduction, data processing, and concluding. This study concludes that the mathematical problem-solving ability of class VIII B students is included in the medium category. Likewise, students' learning independence is included in the medium category. Therefore, there is a relationship between learning independence and mathematical problem-solving abilities of class VIII B students in Eliciting Activities Model (MEAs) for flat-sided building materials. Keywords: mathematical problem-solving ability, self-regulated learning.